TRIM65 regulates innate immune signaling by enhancing K6-linked ubiquitination of IRF3 and its chromatin recruitment - Danae Fonseca; Giuseppe Pisanelli; Rocío Seoane; Lisa Miorin; Adolfo García-Sastre (Cell Reports)
Summary: Viral infection triggers a rapid and effective cellular response primarily mediated by interferon β (IFNβ), which induces an antiviral state through complex signaling cascades. To maintain a robust antiviral response while preventing excessive activation, the induction of IFNβ and downstream signaling are tightly regulated. Members of the tripartite-motif (TRIM) family of E3 ubiquitin (Ub) ligases play crucial roles in modulating these processes. In this study, we demonstrate that TRIM65 interacts with interferon regulatory factor 3 (IRF3), a key transcription factor downstream of multiple innate immune signaling pathways, to regulate type-I IFN production. Specifically, TRIM65 activation enables interaction of TRIM65 BBCC domain with the IAD domain of IRF3. This interaction increases K6-linked ubiquitination of IRF3, enhancing IRF3 recruitment to chromatin and subsequent binding to the IFNβ promoter. This process boosts the expression of IFNβ and interferon-stimulated genes (ISGs), thereby strengthening the control of viral infection.